Design of a Thermal Conductivity Measurement Technique for Clay Furnace Materials Using an Arduino-Based Thermocouple SensorÂ¬ - Elfiana Elfiana; Salmawaty Tansa; Dewa Gede Eka Setiawan (Jurnal Fisika Unand, 2023)
This study aims to design a thermal conductivity measurement system for solid clay furnace materials, measure the thermal conductivity value of a clay furnace using an Arduino-based Thermocouple sensor, and determine the relationship of the thermal conductivity value to variations in clay furnace samples using an Arduino-based thermocouple sensor. The method used in research, design, manufacture and testing of tools. Data collection in this study was to measure the thermal conductivity of 4 samples of clay furnaces based on differences in husks using an Arduino-based Thermocouple sensor. Analysis of research data was carried out using descriptive statistics and inferential statistics, assisted by Microsoft Excel and SPSS programs. In data analysis, univariate, bivariate analysis was performed. The relationship between the value of thermal conductivity to the husk material in each sample has a positive relationship between time and temperature variables, in other words, the more time the temperature increases, the faster the temperature increases. From the results of the study, it can be concluded that the best thermal conductivity is in sample one with a value of 1.5375 J/ (K.m) and the poorest is in sample four with the lowest conductivity value of 0.3125 J/ (K.m).